2013
DOI: 10.1371/journal.pone.0080310
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Antibody Responses to Infections by Chlamydia abortus Enables Identification of Potential Virulence Factors and Candidates for Serodiagnosis

Abstract: Enzootic abortion of ewes (EAE) due to infection with the obligate intracellular pathogen Chlamydia (C.) abortus is an important zoonosis leading to considerable economic loss to agriculture worldwide. The pathogen can be transmitted to humans and may lead to serious infection in pregnant women. Knowledge about epidemiology, clinical course and transmission to humans is hampered by the lack of reliable diagnostic tools. Immunoreactive proteins, which are expressed in infected animals and humans, may serve as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 32 publications
3
34
0
3
Order By: Relevance
“…Here, we have demonstrated that virulence-associated antibodies are generated predominantly in animals that have aborted. This report therefore confirms the observation that virulence-associated proteins, including the newly described SINC homolog of C. abortus (CAB063), are immunogenic in ovine abortion (10). Although ewes that have aborted are considered protected from further abortion due to C. abortus, they represent a major reservoir of the pathogen for animals and humans and therefore need to be rapidly identified.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Here, we have demonstrated that virulence-associated antibodies are generated predominantly in animals that have aborted. This report therefore confirms the observation that virulence-associated proteins, including the newly described SINC homolog of C. abortus (CAB063), are immunogenic in ovine abortion (10). Although ewes that have aborted are considered protected from further abortion due to C. abortus, they represent a major reservoir of the pathogen for animals and humans and therefore need to be rapidly identified.…”
Section: Discussionsupporting
confidence: 83%
“…CPAF was initially described as a chlamydial protease degrading host cell transcription factors; however, its impact on virulence and pathogenicity is currently controversially discussed (20). SINC is a type III secreted protein targeting the nuclear membrane of infected cells, which may modulate the nuclear envelope function (10,11). Here, we have demonstrated that virulence-associated antibodies are generated predominantly in animals that have aborted.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations